Elemental Qualification of Welded Stainless Steels By XRF Positive Material Identification - Mutiarani Mutiarani; Afiev Ferdilla Sidiq; Adhe Aryswan; Mega Gemala; Tian Havwini (Jurnal Teknologi dan Riset Terapan (JATRA), 2022)
Tests for determining the elemental composition of stainless steel (SS) in the weld metal and Heat Affected Zone (HAZ) were carried out using the Non-Destructive Evaluation (NDE) Positive Material Identification (PMI) method with X-ray Fluorescence (XRF) technology. This study aimed to identify the chemical composition of metals using the PMI method with XRF technology as a determinant of the feasibility of the stainless-steel materials tested, namely SS 316 and SS 2205. The results of the tests were then matched with the applicable standards, namely ASME Section II Part A for pipe materials and ASME Section II Part C for welding electrodes. The measurement results show that SS 316 with welding electrode grade ER 316 all parts of the object of inspection fall within the standard range used except for material 4, which is the connection between the flange and elbow is declared rejected because the values ​​for Cr, Ni, and Mo do not fall within the standard range. Meanwhile, SS 2205 with a welding electrode grade of ER 2594 shows that all parts of the object being measured meet the requirements of the standard range used.